The synthesis, photochemical and biological properties of new silicon phthalocyanines - Uslan, Canan; Sesalan, B. Sebnem (Elsevier BV, 2013)
Abstract Bis[(1-methylpyrrolidin-2-yl)methoxy] [phthalocyaninato] silicon ( 2 ), bis[2-azepan-1-yl)ethoxy] [phthalocyaninato] silicon ( 3 ) and bis[(2,4,6-tris( N , N -dimethylamminomethyl) phenoxy)] [phthalocyaninato] silicon ( 4 ) were prepared and they were quaternized with the excess of iodomethane to obtain the compounds 2Q , 3Q and 4Q respectively. The binding of quaternized 2Q , 3Q and 4Q phthalocyanines (pcs) with calf thymus (CT) DNA was investigated by UV–Vis, fluorescence spectrophotometric methods and gel electrophoresis. The quenching effect of all quaternized pcs on the fluorescence intensity of SYBR Gold (SYBR)–DNA complex was determined. The results indicated that novel pcs exhibit efficient DNA binding activity. Photocleavage of CT-DNA in the presence of 2Q , 3Q and 4Q were determined using gel electrophoresis. All the experimental data proved that these pcs might be the candidates as DNA-targetting PDT agents.